Exploring the intersectionality of culture, sacrificial offering, and exploitative prosperity gospel rhetoric in Africa - Udechukwu, Judith I. (Church, Communication and Culture, 2021)
Research has well documented the evidence of the growth of prosperity gospel churches across the globe, but there is a dearth of studies that investigate the interface between culture and exploitative rhetoric among African prosperity gospel ministers. Examining the concept of making sacrificial offerings in the traditional African context, I theorize that culture has significant influence on the exploitative power of prosperity gospel ministers by the following considerations: the African tradition of consulting oracles for solution to spiritual and physical problems, the cultural practice of making sacrificial offerings to the gods in exchange for favor, and the poor socio-economic condition of many prosperity gospel adherents in Africa. This study highlights the use of the rhetoric of spiritual engagement and liberation for audience manipulation, examines the idea of the pure gift, proposes some ethical questions that should govern the prosperity movement, and underscores the need for scholarly engagement.
free
Keywords: Africa; Prosperity gospel; culture; rhetoric; sacrificial offering